TWO CASES OF TRANS-ILIAC TRANS-SACRAL SCREW FIXATION FOR ROMMENS CLASSIFICATION IVb FRAGILITY FRACTURE OF PELVIC RING IVb - MATSUOKA, Tatsuki; ICHIMORI, Siina; KAGIWARA, Muneta; INAGAKI, Naoya; SASAMOTO, Shohei; HAO, Motoshi; SAITO, Mitsuru; NISHIZAWA, Go (Journal of the Japanese Association for the Surgery of Trauma, 2025)
The incidence of fragility fractures of the pelvis (FFP) due to low-energy trauma is increasing in the elderly. Particularly, H- and U-type fractures of FFP type IVb according to the Rommens classification, which are characterized by spinopelvic dissociation, often require spinopelvic fixation. However, in elderly patients with multiple comorbidities, minimally invasive treatments are preferred, such as trans-iliac trans-sacral (TTS) screw fixation. We encountered 2 cases of FFP type IVb fractures treated with TTS screw fixation. Both cases involved H-type fractures, with high-level horizontal fractures at the S2 level. Two TTS screws were inserted into the S1 vertebra, and walking with full weight-bearing was permitted immediately postoperatively. Bone union was achieved at 6 months postoperatively, and the patients returned to their pre-injury level of activities of daily living. While meticulous preoperative planning and reassessment of technical skills are necessary, favorable clinical outcomes can be achieved if two TTS screws are appropriately inserted.